Analysis of Breaststroke Technique in Children Aged 8 -12 Years - Alvyani, Ilvy; Amrulloh, Aziz (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study investigated the conformity of breaststroke swimming technique in 8-12-year-old students at SD Islam Al-Azhar 14 Semarang, recognizing that efficient technical mastery is crucial for optimal swimming performance and minimizing water resistance. Initial observations indicated common errors in breaststroke mechanics, particularly concerning body position and arm/leg movements during the start glide. This quantitative descriptive study involved 15 students from the swimming extracurricular program. Data were collected via video recordings of their breaststroke movements, subsequently analyzed using Kinovea software version 0.9.5 to objectively measure kinematic parameters, specifically arm and leg angles during the start glide phase. The results revealed an average arm angle of 131.4° (± 1.1°) and an average leg angle of 123.6° (± 1.2°) during the glide. These findings indicate that most students had not yet fully achieved the ideal streamline position, essential for maximizing glide efficiency. The observed deviations underscore the critical need for targeted coaching that provides specific, continuous visual and kinesthetic feedback. The study concludes that most students have not yet fully achieved the ideal streamline position crucial for minimizing drag and maximizing glide efficiency.